Succinate at the Crossroad of Metabolism and Angiogenesis: Roles of SDH, HIF1α and SUCNR1 - Reham Atallah; Andrea Olschewski; Akos Heinemann (Biomedicines, 2022)
Angiogenesis is an essential process by which new blood vessels develop from existing ones. While adequate angiogenesis is a physiological process during, for example, tissue repair, insufficient and excessive angiogenesis stands on the pathological side. Fine balance between pro- and anti-angiogenic factors in the tissue environment regulates angiogenesis. Identification of these factors and how they function is a pressing topic to develop angiogenesis-targeted therapeutics. During the last decade, exciting data highlighted non-metabolic functions of intermediates of the mitochondrial Krebs cycle including succinate. Among these functions is the contribution of succinate to angiogenesis in various contexts and through different mechanisms. As the concept of targeting metabolism to treat a wide range of diseases is rising, in this review we summarize the mechanisms by which succinate regulates angiogenesis in normal and pathological settings. Gaining a comprehensive insight into how this metabolite functions as an angiogenic signal will provide a useful approach to understand diseases with aberrant or excessive angiogenic background, and may provide strategies to tackle them.